Evaluation of Cancer Immunity in Mice - Disis, Mary L. (2014)
There have been significant advances in the development and application of novel therapeutic approaches and improved diagnostics for cancer in the past decade. Manipulation and/or assessment of cancer-specific immunity have been central to these advances. Murine models are a standard for the preclinical development of cancer immunotherapeutics. However, critical advances in our understanding of the role of the immune microenvironment and the assessment of cancer-specific immunity have not been fully applied to rodent models. Methods to preserve the function of immune cells after cryopreservation and standard approaches to quantitative immune assays have not been developed. Furthermore, a detailed evaluation of the immune tumor environment, which can impact a clinical response to different agents, is rarely undertaken as models are being contemplated. Rapid translation of immunoncology agents to the clinic will require standardization of immunologic assay methods and a more detailed immunologic characterization of common mouse models. Outlined here are the critical elements in assessing immunity in cancer mouse models and suggestions concerning the standardization of approaches when using these models for the study of immunoncology.